Studies in Pediatric Hearing Loss at the House Research Institute - Eisenberg, Laurie S. (2012)
Three clinical research projects are described that are relevant to pediatric hearing loss. The three projects fall into two distinct areas. The first area emphasizes clinical studies that track developmental outcomes in children with hearing loss; one project is specific to cochlear implants and the other to hearing aids. The second area addresses speech perception test development for very young children with hearing loss. Although these two lines of research are treated as separate areas, they begin to merge as new behavioral tests become useful in developing protocols for contemporary studies that address longitudinal follow-up of children with hearing loss.